Designing specific cheese-ripening ecosystems to shape the immune effects of dairy products?. (January 2015) - Plé, Coline; Adouard, Nadège; Breton, Jérôme; Dewulf, Joëlle; Pot, Bruno; Bonnarme, Pascal; Foligné, Benoit
Highlights: Ripened cheese strains elicit distinct immune responses in vitro . Selected microbial consortia can induce opposite immune responses in vitro . Some cocktails of cheese-strains can exacerbate experimental colitis in mice. Designed cheeses may partly predict inflammatory response in vivo . Key role of cheese's immune profile for risk assessment in IBD patients. Abstract: Although large numbers of viable microorganisms are ingested in ripened cheese, little is known about the microbial ecosystems' influence on the host's immune responses. We designed experimental smear-ripened cheeses with bacteria and yeasts that have opposite immune effects and evaluated their impact in the dextran sulphate sodium (DSS) and trinitrobenzene sulphonic acid (TNBS) colitis mouse models. Mice were fed with a control diet, a milk matrix or with lab-designed, 28-day-ripened prototype soft cheeses A and B (CheA and CheB) from cow milk that respectively hosted consortia of immuno-enhancing and immuno-modulatory microbial strains. Inflammatory markers and transcriptional signatures were evaluated in healthy mice colitic mice. In the DSS colitis model, there were no differences between CheA and CheB in terms of the inflammatory read-outs. In contrast, CheA (but not CheB) exacerbated weight loss and colon lesions in the TNBS model suggesting that designer cheeses may provide opportunities for diet management.